HAS DIETARY INTAKE CHANGED THE CARDIOMETABOLIC RISK DURING COVID-19 LOCKDOWNS AMONG A SAMPLE OF MALAYSIAN ADULTS? - Chiang WL; Barakatun Nisak MY; Azrina A; Irmi ZI; Zalina AZ (Proceeding B-ICON, 2022)
Metabolic syndrome (MetS) is a measure of an individual’s risk of developing diseases such as type 2 diabetes and cardiovascular disease. Due to the COVID-19 lockdowns in Malaysia, the dietary intake among Malaysians might have changed, influencing the cardiometabolic risk. The impact of COVID-19 lockdowns on MetS and dietary intake is unknown. The present study aimed to investigate the MetS and dietary intake, as well as their association with MetS using an online survey. Methodology: This web-based cross-sectional study was conducted using self-administered questionnaires. The habitual dietary intake was determined using a thirty-seven-item Singapore Short Diet Screener. The MetS was investigated using the Asian Modified Finnish Diabetes Risk Score Questionnaire. A total of 209 respondents (43 males, 166 females) was included in the study. About 41.1% (n=86) of them aged between 30 to 60 years old, 79.4% (n=166) were female, 67.0% (n=140) were single, 57.4% (n=120) were not working, 95.2% (n=199) had tertiary education and 47.4% (n=99) were from Selangor. The MetS in the population was 39.6% (n=75). The MetS was significantly associated with wholemeal noodles (p=0.033), red meat (p=0.020), other vegetables (p=0.012) and amount of sugars added in coffee (p=0.049). The COVID-19 lockdowns had influenced the dietary intake and MetS of Malaysian adults. The relevant authorities should take this seriously since it attributes to the rising of non-communicable disease.